Ductal epithelial expression of Ro52 correlates with inflammation in salivary glands of patients with primary Sjögren's syndrome. (July 2014) - Aqrawi, L. A.; Kvarnström, M.; Brokstad, K. A.; Jonsson, R.; Skarstein, K.; Wahren‐Herlenius, M.
Summary Ro52 is an E3 ubiquitin ligase with a prominent regulatory role in inflammation. The protein is a common target of circulating autoantibodies in rheumatic autoimmune diseases, particularly Sjögren's syndrome (SS). In this study we aimed to investigate the expression of the SS target autoantigen Ro52 in salivary glands of patients with primary Sjögren's syndrome (pSS). Ro52 expression was assessed by immunohistochemical staining of paraffin‐embedded and frozen salivary gland biopsies from 28 pSS patients and 19 non‐pSS controls from Swedish and Norwegian registries, using anti‐human Ro52 monoclonal antibodies. The degree and pattern of staining and inflammation was then evaluated. Furthermore, secreted Ro52 protein was measured in saliva and serum samples from the same individuals through a catch‐enzyme‐linked immunosorbent assay (ELISA). Ro52 was highly expressed in all the focal infiltrates in pSS patients. Interestingly, a significantly higher degree of Ro52 expression in ductal epithelium was observed in the patients compared to the non‐pSS controls (P < 0·03). Moreover, the degree of ductal epithelial expression of Ro52 correlated with the level of inflammation (Spearman's r = 0·48, P < 0·0120). However, no secreted Ro52 protein could be detected in serum and saliva samples of these subjects. Ro52 expression in ductal epithelium coincides with degree of inflammation and is up‐regulated in pSS patients. High expression of Ro52 might result in the breakage of tolerance and generation of Ro52 autoantibodies in genetically susceptible individuals. We conclude that the up‐regulation of Ro52 in ductal epithelium might be a triggering factor for disease progression in SS.